PENGARUH POLA KOMUNIKASI DAN INTERAKSI KADER TERHADAP KEMAJUAN RODA ORGANISASI MEDAN BERNALAR - Rena Afrida Lubis (LP2M Universitas Bina Bangsa, 2022)
The Field Work Practice II (PKL) conducted by the practitioner aims to solve the problems that exist in the Reasoning Field Organization. Problem solving is carried out using the Mezzo (organization/community) level Intervention method which has several stages in general: 1) Assessment Stage 2) Planning Stage 3) Intervention or Program Implementation Stage 4) Evaluation Stage. Practitioners as social workers have roles in this regard, namely: 1) Providing assistance to clients starting from the assessment stage to the evaluation stage 2) as facilitators, in terms of facilitating clients 3) as consultants for clients if there is a decision making. The subject of this research is the Management of the Medan Reasoning Organization. Data collection was carried out starting from observation, interview, and documentation techniques. In the assessment stage, there are tools used to assist clients in finding the root of the problem, namely using the Participatory Learning and Action (PLA) Method, an approach to the learning process and interacting with the community and society. The implementation of program activities will change, although not significantly. Practitioners and clients will go through an evaluation stage where this stage will provide an assessment of the activities and programs that are being implemented.